Penggunaan ekstrak bawang putih untuk menanggulangi bakteri Aeromonas hydrophyla yang menyerang benih ikan Nila (Oreochromis niloticus) - Leni Handayani; S Siswanto (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2019)
This study aims to determine how the effect of garlic extract on the bacteria Aeromonas hydrophyla that attacks Nile Tilapia (Oreochromis niloticus) seeds. This study used 4 treatments and 3 replications. The treatments used were treatment A (use of garlic extract by giving it by immersion), treatment B (use of garlic extract by oral administration), treatment C (use of garlic extract by injection) and treatment D (without giving extract). The parameters observed in this study were clinical symptoms and wound healing, survival and water quality as supporting parameters. The results showed that the administration of garlic extract gave an influence on the percentage of wound healing and survival rate of Nile Tilapia seeds. Based on the research results, the effective method that can be used for administration of garlic extract is through feed (oral administration). Water quality during the maintenance period can still be tolerated by Nile Tilapia seeds. Keywords : Aeromonas, garlic, Nile Tilapia.